Antistatic composition and antistatic polyester film using same

By using conductive polymer resin and other compositions in the antistatic polyester film, the antistatic layer is formed, and the durability problem of the antistatic polyester film under folding display and UV irradiation is solved, and the solvent resistance of the antistatic film is realized and UV resistance, maintaining the stability of surface resistance and water contact angle.

CN119177078APending Publication Date: 2024-12-24TORAY ADVANCED MATERIALS KOREA INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311296435.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-23
Filing Date
2023-10-09
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Antistatic polyester films may experience linear defects in rapidly expanding or folding displays and are not durable to organic solvents and UV irradiation, resulting in reduced or loss of antistatic properties.

Method used

Using an antistatic composition containing conductive polymer resin, binder resin, crosslinking agent, ultraviolet absorber and free radical scavenger, an antistatic layer is formed by mixing a specific proportion to ensure that it remains excellent under organic solvents and UV irradiation conditions. surface resistance and water contact angle.

Benefits of technology

The solvent resistance and UV resistance of the anti-static polyester film are achieved, which prevents static electricity generation and dust accumulation, and maintains the characteristics and appearance quality of the film surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177078A_ABST
    Figure CN119177078A_ABST
Patent Text Reader

Abstract

Provided are an antistatic composition and an antistatic polyester film using the same, the antistatic polyester film comprising: a polyester substrate; and an antistatic layer formed by applying an antistatic composition to at least one surface of the polyester substrate, the antistatic composition comprising a conductive polymer resin, a binder resin, a crosslinking agent, an ultraviolet light absorber, and a radical scavenger. According to the present invention, by providing an antistatic layer having antistatic performance while also having solvent resistance and UV resistance, excellent surface resistance can be maintained during a secondary processing process involving organic solvent or UV irradiation, and a change in a water contact angle can be minimized, thereby maintaining characteristics of a film surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an antistatic polyester film having excellent durability, and more particularly, to an antistatic composition having excellent UV resistance and solvent resistance and an antistatic polyester film using the same. Background Art

[0002] Generally, polyester film is excellent in dimensional stability, thickness uniformity and optical transparency. Therefore, due to its wide range of applications, it is widely used in various industries including electronic and electrical industries, display industry and automotive industry as various industry materials and equipment. However, despite the excellent physical properties, the disadvantage of polyester film is that the film surface has a very high resistance, and is therefore easily charged when friction is applied. In this case, an electrical short circuit is applied to the film surface by static electricity, which may cause defects or cause foreign matter (such as dust) to be attached to the film surface, resulting in product defects. In order to solve these problems, research is actively carried out to enhance antistatic function. Generally, antistatic film prevents the phenomenon of charge accumulation on the film surface by giving an antistatic layer on the film, and it is widely used due to its excellent antistatic performance.

[0003] With the recent development of the display industry, the demand for antistatic films has grown, leading to the emergence of multiple types of antistatic films using different antistatic mechanisms. Among them, the most commonly used type is the low-cost anionic antistatic type. In addition, as the market for high-quality films expands, the demand for antistatic films using conductive polymers has also increased.

[0004] Such conductive polymers are commonly used in antistatic polyester films due to their excellent transparency and antistatic properties. However, when applied to optical biaxially stretched polyester films used in rapidly expanding flexible or foldable displays, linear defects may occur in specific areas due to folding or bending. Therefore, this may lead to damage to the film coating and subsequent reduction or loss of antistatic properties. In addition, when a secondary coating is applied using chemicals such as organic solvents, there may be a problem of lack of solvent resistance in the antistatic coating, resulting in an increase in surface resistance. In the process of coating with a UV-curable pressure-sensitive adhesive or adhesive, there may also be a problem that the antistatic coating on the film may deteriorate during UV irradiation and cause bonding with a UV-curable resin. Summary of the invention

[0005] Technical issues

[0006] The present invention is designed to solve various problems including the above-mentioned problems, and an object of the present invention is to provide an antistatic composition and an antistatic polyester film using the same, the antistatic composition making it possible to provide an antistatic layer having antistatic properties while also having solvent resistance and UV resistance, thereby maintaining excellent surface resistance and minimizing changes in water contact angle during a secondary processing process involving an organic solvent or UV irradiation to maintain the characteristics of the film surface.

[0007] The above and other objects and advantages of the present invention will become apparent from the following description of the preferred embodiments.

[0008] Technical Solution

[0009] The above object is achieved by an antistatic composition comprising a conductive polymer resin, a binder resin, a crosslinking agent, an ultraviolet absorber and a radical scavenger.

[0010] Preferably, the conductive polymer resin may include an aqueous dispersion containing a polyanion and polythiophene or an aqueous dispersion containing a polyanion and a polythiophene derivative.

[0011] Preferably, the average particle size of the conductive polymer resin may be 20 nm to 60 nm.

[0012] Preferably, the binder resin may include at least one selected from polyurethane, polyester, and acrylic.

[0013] Preferably, the crosslinking agent may include a crosslinking agent selected from the group consisting of an isocyanate-based crosslinking agent, a carbodiimide-based crosslinking agent, a At least one of an oxazoline-based crosslinking agent, an epoxy-based crosslinking agent, and a melamine-based crosslinking agent.

[0014] Preferably, the ultraviolet absorber may include a benzotriazole-based compound or a benzophenone-based compound, and more preferably, the ultraviolet absorber may include at least one compound selected from the group consisting of 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylmethyl)phenol, bis[2-hydroxy-5-tert-octyl-3-(benzotriazole-2-yl)-phenyl]-methane, 2(2'-hydroxy-3,5' -di-tert-butylphenyl)benzotriazole, 2(2'-hydroxy-3'-tert-butyl-5'-methyl-phenyl)benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone and 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol].

[0015] Preferably, the radical scavenger may be a hindered amine-based light stabilizer having an amine functional group, and may be a polymerization product having a 2,2,6,6-tetramethylpiperidine skeleton.

[0016] Preferably, the antistatic composition may include 150 to 400 parts by weight of the binder resin and 200 to 800 parts by weight of the cross-linking agent based on 100 parts by weight of the conductive polymer resin.

[0017] Preferably, the weight ratio between the binder resin and the cross-linking agent may be 1:1 to 4.

[0018] Preferably, the antistatic composition may include 15 to 40 parts by weight of the total UV absorber and the radical scavenger relative to 100 parts by weight of the binder resin.

[0019] Furthermore, the above object is achieved by an antistatic polyester film comprising a polyester base and an antistatic layer formed by applying the above antistatic composition to at least one surface of the polyester base.

[0020] Preferably, the surface resistance of the antistatic layer can be 10 7 Ω / sq or less.

[0021] Preferably, the antistatic layer may show a surface resistance change ΔH1 according to the following Formula 1 of 1 or less before and after UV irradiation with a dose of 300 mJ or more.

[0022] (Formula 1)

[0023] ΔH1=log[(UV2) / (UV1)]

[0024] Here, UV1 is the surface resistance before UV irradiation, and UV2 is the surface resistance after UV irradiation.

[0025] Preferably, the antistatic layer may show a difference in water contact angle of 1.9° or less before and after UV irradiation with a dose of 300 mJ or more.

[0026] Preferably, the antistatic layer may show a surface resistance change ΔH2 according to the following Formula 2 of 1.8 or less before being immersed in the MEK solvent and after being immersed in the MEK solvent for 2 hours.

[0027] (Formula 2)

[0028] ΔH2=log[(MEK2) / (MEK1)]

[0029] Here, MEK1 is the surface resistance before MEK immersion, and MEK2 is the surface resistance after MEK immersion.

[0030] Beneficial Effects

[0031] The antistatic composition and the antistatic polyester film using the same according to one embodiment of the present invention relate to an antistatic film having excellent solvent resistance and UV resistance, and can effectively prevent dust accumulation from the environment and reduce static electricity generation. In addition, it provides technical benefits such as preventing damage to the antistatic layer during secondary processing involving organic solvents and UV irradiation, thereby maintaining excellent surface resistance and water contact angle.

[0032] However, those skilled in the art will appreciate that the effects that can be achieved by the present invention are not limited to the above specific description, and other advantages of the present invention will be more clearly understood from the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is a block diagram of an antistatic polyester film according to one embodiment of the present disclosure. DETAILED DESCRIPTION

[0034] Hereinafter, exemplary embodiments of the present invention will be described more fully with reference to the accompanying drawings so that those skilled in the art can easily put the present invention into practice. The present invention can be implemented in many different forms and should not be construed as being limited to the embodiments set forth herein.

[0035] Unless otherwise limited, all technical terms and scientific terms used herein have the same meanings as those generally understood by those of ordinary skill in the art to which the present invention belongs. In the event of a conflict, this specification (including limitations) shall prevail. Although those similar or equivalent to the methods and materials described herein may be used in the practice or testing of the present invention, suitable methods and materials are described herein.

[0036] In the present specification, the term "resin based on ...", "polymer based on ..." or / and "copolymer based on ..." is an inclusive concept, which covers "-resin", "-polymer", "-copolymer" or / and "derivatives of-resin, -polymer or -copolymer". In addition, the term "polymer or copolymer cross-linked with these resins" as used herein means "polymer or copolymer cross-linked with the above-mentioned resin".

[0037] The term "compound" as used herein is a comprehensive concept that encompasses "monoatomic molecules", "oligomers", and "polymer compounds including both homopolymers and copolymers".

[0038] In this specification, unless explicitly stated to the contrary, the terms "comprise", "comprising", "including", "including", "containing", "characterized by", "having", "having" or any other variations thereof will be understood to mean the inclusion of stated elements but not excluding the presence or addition of one or more other elements.

[0039] As used herein, the term "and / or" is intended to include any and all combinations of one or more items listed in connection therewith. The term "or" used herein means "and / or". In this specification, the expression "at least one" or "one or more" used before a component is intended to supplement the list of all component elements, and does not mean to supplement the single component described.

[0040] Unless otherwise stated, all percentages, parts, ratios, etc. are by weight. When an amount, concentration, or other value or parameter is given as a range, a preferred range, or a list of preferred upper values ​​and preferred lower values, this should be understood as specifically disclosing all ranges formed by any pair of any upper range or preferred value and any lower range or preferred value, whether or not a range is disclosed individually.

[0041] Where numerical ranges are recited herein, unless otherwise indicated, the ranges are intended to include their endpoints, as well as all integers and fractions within the range. When defining a range, it is not intended that the scope of the invention be limited to the specific values ​​recited.

[0042] In the present specification, each of the components includes both the singular and the plural forms.

[0043] About the antistatic composition according to the present invention and the antistatic polyester film using it, the inventor has found through diligent research on the shortcomings of conventional technology that when the antistatic layer is formed by mixing a modified conductive composite material, a crosslinking agent, a binder, an ultraviolet (UV) absorber and a free radical scavenger with excellent antistatic performance in a specific ratio, excellent appearance quality, excellent antistatic performance, solvent resistance, UV resistance and various other excellent characteristics are obtained. Based on these findings, the inventor has completed the present invention. Hereinafter, the antistatic composition according to one embodiment of the present invention and the antistatic polyester film using it will be described in detail.

[0044] Figure 1 is a block diagram of an antistatic polyester film according to one embodiment of the present disclosure.

[0045] Reference Figure 1, an antistatic polyester film according to one embodiment of the present invention includes a polyester substrate 10 and an antistatic layer 20 formed by applying an antistatic composition to at least one surface of the polyester substrate, wherein the antistatic composition contains a conductive polymer resin, a binder resin, a crosslinking agent, a UV absorber, and a radical scavenger.

[0046] Figure 1 The antistatic polyester film is shown to have only one antistatic layer 20 formed on the upper surface of the substrate 10. However, the present invention is not limited thereto, and the antistatic layer 20 may be formed on the upper or lower surface of the substrate 10, or on both surfaces (upper and lower surfaces).

[0047] 1. Base 10

[0048] The substrate 10 is preferably a film made of a polyester resin. The type of film used for the substrate 10 is not particularly limited, and those known in the art as substrate films for antistatic coatings can be used.

[0049] The polyester resin forming the substrate 10 is preferably a polyester obtained by polycondensing aromatic dicarboxylic acids and aliphatic diols. Here, aromatic dicarboxylic acids may include terephthalic acid, 2,6-naphthalene dicarboxylic acid, etc. Examples of other dicarboxylic acid components of copolymerized polyesters may include isophthalic acid, phthalic acid, terephthalic acid, 2,6-naphthalene dicarboxylic acid, adipic acid, sebacic acid, oxycarboxylic acid (for example, p-hydroxybenzoic acid), etc. Examples of aliphatic diols may include ethylene glycol, diethylene glycol, 1,4-cyclohexanedimethanol, propylene glycol, butanediol, neopentyl glycol, etc. Dicarboxylic acid components and diol components may be used in combinations of two or more thereof. Representative polyester films include polyethylene terephthalate (PET), polyethylene 2,6-naphthalene dicarboxylate (PEN), and copolymers containing a third component in the above-mentioned polyesters are also possible.

[0050] In the present disclosure, although the components constituting the substrate 10 are described mainly focusing on polyester resins such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, the substrate 10 of the present invention is not limited to these resins.

[0051] 2. Antistatic layer 20

[0052] The antistatic layer 20 is formed by applying an antistatic composition on at least one surface of the substrate 10. The antistatic composition may include a conductive polymer resin, a binder resin, a crosslinking agent, a UV absorber, and a radical scavenger.

[0053] In one embodiment, conductive polymer resin is used to realize antistatic properties. The conductive polymer resin contained in the antistatic composition according to one embodiment of the present invention is preferably an aqueous dispersion containing polyanions and polythiophene or an aqueous dispersion containing polyanions and polythiophene derivatives, to impart excellent antistatic properties (low surface resistance and high conductivity). Here, the polyanion is an acidic polymer, and preferably includes at least one selected from polycarboxylic acid, polysulfonic acid and polyvinyl sulfonic acid. In addition, for example, polycarboxylic acid preferably includes at least one selected from polyacrylic acid, polymethacrylic acid and polymaleic acid, and polysulfonic acid preferably includes polystyrene sulfonic acid.

[0054] In the present invention, in the conductive polymer resin used, it is preferred that polythiophene or polythiophene derivatives have an excess weight ratio of solid polyanions to impart conductivity. For example, when 1 wt% of polythiophene or polythiophene derivatives are used, the polyanions are preferably present in an amount greater than 1 wt% and less than or equal to 5 wt%, and more preferably greater than 1 wt% to less than 3 wt%. In this regard, in the embodiments of the present invention to be described below, an aqueous dispersion containing 0.5 wt% of poly(3,4-ethylenedioxythiophene) and 0.8 wt% of polystyrene sulfonic acid (molecular weight Mn=150,000) is used, but this is merely an example, and the present invention is not limited thereto.

[0055] In addition, the average particle size of the conductive polymer resin is preferably 20nm to 60nm, and more preferably 20nm to 50nm. The conductive polymer resin is distributed with the above-mentioned particle size so that the antistatic layer 20 shows stable antistatic performance. When the average particle size of the conductive polymer resin exceeds 60nm, after transverse stretching, the position dependence of the surface resistance changes significantly and increases, causing the antistatic durability to deteriorate significantly. On the contrary, when the particle size is less than 20nm, the number of connection points between the conductive polymer resin particles (the contact frequency between different conductive polymer resin particles) increases, causing higher surface resistance. Compared with the conductive polymer resin commonly used in the antistatic layer, the average particle size of the conductive polymer resin as described above is generally less than 20% or less. Any known method that can physically reduce the particle size can be used without restriction, and commercially available products that meet the above-mentioned size standard can also be used.

[0056] In one embodiment, the binder resin included in the antistatic composition according to the present invention may include at least one selected from polyurethane, polyester and acrylic acid. In these binder resins, polyurethane resin is particularly preferred. When resin layer or functional layer are added to the antistatic layer by secondary processing, such polyurethane resin plays the effect of enhancing the adhesion between antistatic layer 20 and the resin layer or the functional layer.

[0057] This polyurethane resin is of aqueous dispersion type, and preferably consists of a resin composed of an anionic polyether polyurethane dispersion containing at least one functional group (e.g., hydroxyl, amine, alkyl, and carboxyl). More specifically, the water-dispersible polyurethane resin includes: an anionic polyether polyurethane dispersion containing a hydroxyl group; an anionic polyether polyurethane dispersion containing a functional group of at least one repeating unit selected from the following: allylamine, vinylamine, ethyleneamine, vinylpyridine, diethylaminoethyl methacrylate, diallyldimethylammonium chloride, methacryloyloxyethyltrimethylammonium sulfate, and combinations thereof; or an anionic polyether polyurethane dispersion containing a functional group of at least one repeating unit selected from the following: methyl, ethyl, propyl, butyl, pentyl, hexyl, and combinations thereof.

[0058] In one embodiment, a crosslinking agent contained in the antistatic composition according to the present invention is used to control the crosslinking density of the antistatic composition and improve the durability and coating properties of the antistatic layer 20 and the antistatic polyester film. In this case, the crosslinking agent may include a crosslinking agent selected from the group consisting of isocyanate-based, carbodiimide-based, At least one of oxazoline, epoxy-based and melamine-based components.

[0059] In one embodiment, it is preferred that the UV absorber contained in the antistatic composition according to the present invention contains a benzotriazole-based compound or a benzophenone-based compound. More specifically, the UV absorber preferably includes at least one compound selected from the group consisting of 2-(2H-benzotriazol-2-yl)-4,6-bis(1-methyl-1-phenylmethyl)phenol, bis[2-hydroxy-5-tert-octyl-3-(benzotriazol-2-yl)phenyl]methane, 2(2'-hydroxy-3,5'-di-tert-butylphenyl)benzotriazole, 2(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone and 2,2'-methylenebis[6-(2H-benzotriazol-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol].

[0060] In one embodiment, the radical scavenger contained in the antistatic composition according to the present invention is preferably a hindered amine-based light stabilizer having an amine functional group, and more preferably a polymerization product having a 2,2,6,6-tetramethylpiperidine skeleton. Such a hindered amine-based light stabilizer does not have ultraviolet absorption capability, but acts as a radical scavenger, which effectively captures free radicals generated when the binder (particularly the polyurethane binder) in the antistatic layer 20 undergoes photolysis due to UV irradiation, preventing the antistatic layer 20 from being degraded due to UV exposure.

[0061] In one embodiment, the antistatic composition preferably includes 150 to 400 parts by weight of a binder resin and 200 to 800 parts by weight of a crosslinking agent, based on 100 parts by weight of the conductive polymer resin.

[0062] In the antistatic composition, when the content of the binder resin is less than 150 parts by weight, the adhesion between the substrate 10 and the antistatic layer 20 is reduced, resulting in weakening and deterioration of the solvent resistance of the antistatic layer 20. On the other hand, when the content of the binder resin exceeds 400 parts by weight, the amount of the conductive polymer resin may be relatively insufficient, resulting in an increase in surface resistance, which may deteriorate the antistatic performance.

[0063] In addition, in the antistatic composition, when the content of the crosslinking agent is less than 200 parts by weight, the crosslinking density of the antistatic layer 20 is reduced, resulting in reduced adhesion to the substrate 10, and weakened and deteriorated solvent resistance of the antistatic layer 20. On the other hand, when the content of the crosslinking agent exceeds 800 parts by weight, the crosslinking density is too large, and the desired surface resistance cannot be achieved, resulting in a significant change in the water contact angle caused by irradiated UV and a poor appearance.

[0064] In addition, the weight ratio between the binder resin and the crosslinking agent in the antistatic composition is preferably 1: 1 to 4. When the weight ratio is less than 1: 1, the relatively insufficient crosslinking agent may cause the crosslinking density of the antistatic layer 20 to decrease, thereby causing the adhesion to the substrate 10 to decrease and the solvent resistance of the antistatic layer 20 to weaken and deteriorate. When the weight ratio exceeds 1: 4, the excessive crosslinking agent leads to an excessively large crosslinking density, making it impossible to achieve the desired surface resistance, and causing a significant change in the water contact angle caused by the irradiated UV and surface defects.

[0065] In one embodiment, the antistatic composition preferably comprises 15 to 40 parts by weight of total UV absorbers and free radical scavengers relative to 100 parts by weight of the binder resin. When the total weight of the UV absorber and the free radical scavenger is less than 15 parts by weight, the UV absorption or free radical capture effect may be insufficient, resulting in reduced UV resistance, increased surface resistance, reduced contact angle and deteriorated antistatic performance during UV irradiation. On the other hand, when the total weight of the UV absorber and the free radical scavenger exceeds 40 parts by weight, the physical properties of the film may deteriorate, and the UV absorber and the free radical scavenger may not be evenly dispersed, resulting in deteriorated coating quality and poor appearance.

[0066] In addition, antistatic composition is preferably an aqueous composition using water as a primary solvent. In addition, in order to improve the coatability and transparency for antistatic composition of the present invention, an organic solvent can be included in an appropriate amount that can not adversely affect the effect of the present invention. In this case, preferably use at least one organic solvent selected from isopropyl alcohol, butyl cellosolve, tert-butyl cellosolve, ethyl cellosolve, acetone, ethanol and methanol. However, when a large amount of organic solvents are used in the antistatic composition, when the antistatic composition is applied to substrate 10 by online coating, there is a risk of explosion during drying, stretching processing and thermal treatment process. Therefore, preferably the content of organic solvent in the coating solution is controlled to 10 % by weight or less, and more preferably 5 % by weight or less.

[0067] In addition, in the scope that can not adversely affect effect of the present invention (particularly optical characteristic and antistatic property), except conductive polymer resin, plasticizer, binder resin and crosslinking agent, antistatic composition can comprise multiple additives.For example, the additive added in antistatic composition can comprise surfactant, solvent, antioxidant, heat stabilizer, weathering stabilizer, organic lubricant, dye, pigment, organic / inorganic particle, filler, nucleator etc.Especially, adding inorganic particles in the antistatic composition forming antistatic layer 20 is more preferred, because it can strengthen flow characteristics or anti-blocking property.In this case, antistatic composition preferably comprises one or more inorganic particles selected from silicon dioxide, colloidal silica, aluminum oxide, aluminum oxide sol, kaolin, talcum, mica and calcium carbonate.

[0068] 3. Antistatic polyester film

[0069] The antistatic polyester film according to one embodiment of the present invention includes the above-mentioned polyester base 10 and an antistatic layer 20 formed by applying the above-mentioned antistatic composition to at least one surface of the polyester base 10 .

[0070] In the antistatic polyester film according to one embodiment of the present invention, the antistatic layer 20 preferably has 10 7 Ω / sq or less. When the surface resistance of the antistatic layer 20 exceeds 10 7 Ω / sq, static electricity may be generated due to high surface resistance, resulting in reduced antistatic performance.

[0071] By the composition of the antistatic composition as described above, the antistatic polyester film according to one embodiment of the present invention achieves high UV resistance and high solvent resistance. More specifically, in the antistatic polyester film according to one embodiment of the present invention, before and after UV irradiation with a dose of 300mJ or more, the antistatic layer 20 preferably exhibits a surface resistance change ΔH1 of 1 or less according to the following formula 1.

[0072] (Formula 1)

[0073] ΔH1=log[(UV2) / (UV1)]

[0074] Here, UV1 is the surface resistance before UV irradiation, and UV2 is the surface resistance after UV irradiation.

[0075] When the value of Formula 1 exceeds 1, the surface resistance significantly increases during a secondary processing process involving UV irradiation, resulting in deterioration of antistatic properties.

[0076] Furthermore, in one embodiment of the present invention, it is preferred that the difference in the water contact angle of the antistatic layer 20 before and after UV irradiation with a dose of 300 mJ or more is 1.9° or less. When the difference in the water contact angle before and after UV irradiation exceeds 1.9°, surface contamination or reduction in anti-blocking properties may occur due to a significant change in the water contact angle during a secondary processing process involving UV irradiation, and slip characteristics may become stronger during winding or lamination.

[0077] Furthermore, in the antistatic polyester film according to one embodiment of the present invention, the antistatic layer 20 preferably exhibits a surface resistance change ΔH2 according to the following Formula 2 of 1.8 or less before immersion in the MEK solvent and after immersion in the MEK solvent for 2 hours.

[0078] (Formula 2)

[0079] ΔH2=log[(MEK2) / (MEK1)]

[0080] Here, MEK1 is the surface resistance before MEK impregnation, and MEK2 is the surface resistance after MEK impregnation.

[0081] When the value of Formula 2 exceeds 1.8, the surface resistance significantly increases during a secondary processing process using an organic solvent, resulting in deterioration of antistatic properties.

[0082] Hereinafter, the composition and effects of the present invention will be described in more detail through examples and comparative examples.The following examples are provided to further illustrate the present invention and should not be construed as limiting the scope of the present invention.

[0083] [Example]

[0084] [Examples 1 to 6]

[0085] Step 1: Preparation of antistatic composition

[0086] The antistatic composition was prepared by mixing water with an aqueous dispersion as a conductive polymer resin (AS grade) containing 0.5 wt % of poly(3,4-ethylenedioxythiophene) and 0.8 wt % of polystyrenesulfonic acid (molecular weight Mn=150,000), an anionic polyether polyurethane dispersion as a binder resin containing hydroxyl groups, an epoxy crosslinker (CK-7B, Esprix Technologies) as a crosslinker, a UV absorber (UC-3125, ADEKA Corporation), a radical scavenger (EVERSORB AQ1, CHEMPIA Co., Ltd) and an acetylene glycol-based surfactant (2,5,8,11-tetramethyl-6-dodecyl-5,8-diol ethoxylate) to achieve a solid content of 5.0 wt %. The weight ratio of the UV absorber to the radical scavenger was 1:1, and the contents of the components of the antistatic composition were as shown in Table 1. The surfactant was contained in an amount of 1 part by weight based on 100 parts by weight of the binder resin.

[0087] Step 2: Preparation of uniaxially stretched polyester film

[0088] A polyethylene terephthalate pellet having an intrinsic viscosity of 0.625 dl / g and containing 20 ppm of amorphous spherical silica particles having an average diameter of 2.5 μm was dried at 160° C. for 7 hours using a vacuum dryer. It was then melted and adhered to a cooling drum through an extrusion T-die using an electrostatic application method to produce an amorphous unstretched sheet. The sheet was subsequently heated and stretched 3.5 times its original length in the film travel direction at 95° C. to prepare a uniaxially stretched polyester substrate.

[0089] Step 3: Preparation of biaxially stretched antistatic polyester film

[0090] The antistatic composition prepared in step 1 was coated onto the uniaxially stretched polyester substrate produced in step 2 using a gravure roll. The coated antistatic composition was then dried at a temperature of 105° C. to 140° C. in a region where a tenter was located. Subsequently, the polyester substrate coated with the antistatic composition was stretched four times its original length in the film traveling direction and in a direction perpendicular thereto, and finally heat-treated at 240° C. for 4 seconds to prepare a biaxially stretched antistatic polyester film having a substrate thickness of 75 μm and an antistatic layer thickness of 70 nm.

[0091] [Comparative Example]

[0092] [Comparative Examples 1 to 6]

[0093] An antistatic polyester film was prepared in the same manner as in Example 1, except that the contents of the ingredients of the antistatic composition were as specified in Table 1 below.

[0094] For the antistatic polyester films prepared in Examples 1 to 6 and Comparative Examples 1 to 6, physical properties were evaluated by the following experimental examples, and the results are shown in Tables 1 and 2.

[0095] [Experimental example]

[0096] (1) Measurement of surface resistance

[0097] A4-sized films were sampled from each of the films prepared according to Examples and Comparative Examples, and the surface resistance was measured from the antistatic layer surface of each of the sampled films using a surface resistance measuring device (Model 800, ACL, terminal method).

[0098] (2) Measurement of water contact angle

[0099] A 5 cm*5 cm film was sampled from each of the films prepared according to Examples and Comparative Examples, and the water contact angle on the antistatic layer surface of each sample was measured using a water contact angle measuring device (DROPMASTER 300, KYOWA INTERFACE SCIENCE CO., LTD.) The average value of three measurements was used.

[0100] (3) UV resistance analysis

[0101] After irradiating the surfaces of the antistatic layers of Examples and Comparative Examples with 300 mJ of UV light, the surface resistance and the water contact angle on the surfaces of the antistatic layers were measured in the same manner as in Experimental Examples 1 and 2.

[0102] (4)Solvent resistance analysis

[0103] The examples and comparative examples were immersed in MEK (methyl ethyl ketone) for 2 hours and then taken out. Subsequently, the surface resistance on the surface of the antistatic layer was measured in the same manner as in Experimental Example 1.

[0104] (5) Appearance analysis

[0105] When the antistatic layer coating surfaces of the Examples and Comparative Examples were observed with the naked eye under fluorescent light, the size and number of uncoated areas were compared and evaluated based on the following criteria. Areas exceeding 1 mm*3 mm were considered uncoated, and the reference inspection area was based on 1 m 2 .

[0106] Good: The number of uncoated areas is 0 to 10

[0107] Poor: The number of uncoated areas exceeds 10

[0108] In the following Table 1, A represents a conductive polymer resin, B represents a binder resin, C represents a crosslinking agent, and D represents the total weight of a UV absorber and a radical scavenger in a weight ratio of 1:1. Here, the contents of the binder resin B and the crosslinking agent C are given in parts by weight based on 100 parts by weight of the conductive polymer resin A, and the total weight of the UV absorber and the radical scavenger D is given in parts by weight based on 100 parts by weight of the binder resin B. In addition, the unit of the surface resistance is "Ω / sq" (ohm / square), and the unit of the water contact angle is "°" (degree).

[0109] In addition, in Table 1, "before treatment" indicates Examples and Comparative Examples before any treatment (i.e., before UV irradiation or MEK immersion). "After UV treatment" indicates Examples and Comparative Examples after UV irradiation with a dose of 300 mJ, and "after MEK immersion" indicates Examples and Comparative Examples after immersion in a MEK solution for 2 hours.

[0110] [Table 1]

[0111]

[0112] The measured values ​​in Table 1 were used to calculate the relationship (Formula 1 and Formula 2) and the difference in water contact angle before and after UV treatment and before and after MEK immersion.

[0113] [Table 2]

[0114] Formula 1 Difference in water contact angle Formula 2 Example 1 0.54 1.9 1.72 Example 2 0.56 1.1 1.57 Example 3 0.35 1 1.47 Example 4 0.54 0.1 1.50 Example 5 0.17 0.5 1.02 Example 6 0.91 1.9 1.66 Comparative Example 1 0.57 3.1 2.78 Comparative Example 2 0.83 2 2.57 Comparative Example 3 1.79 8.2 1.96 Comparative Example 4 -0.04 11.2 1.08 Comparative Example 5 1.73 5.6 1.56 Comparative Example 6 0.13 1.9 1.58

[0115] As shown in Table 1 and Table 2 above, the antistatic polyester films according to Examples 1 to 6 satisfying the composition of the present invention have 10 7 Ω / sq or less surface resistance value. In addition, the changes in surface resistance and water contact angle before and after UV treatment and before and after MEK immersion satisfy Formula 1 and Formula 2, providing excellent UV resistance and solvent resistance. The surface characteristics of the antistatic polyester film remain unchanged, and the appearance of the antistatic layer is excellent.

[0116] On the other hand, Comparative Example 1 in which the binder resin content in the antistatic composition was insufficient showed a lack of adhesion in the antistatic layer, resulting in a significant increase in surface resistance after MEK immersion, which did not satisfy Formula 2, indicating insufficient solvent resistance.

[0117] Furthermore, Comparative Example 2 in which the crosslinking agent content in the antistatic composition was insufficient had a low crosslinking density, resulting in reduced adhesion between the antistatic layer and the substrate, which did not satisfy Formula 2, indicating insufficient solvent resistance.

[0118] In addition, Comparative Example 3, in which the crosslinking agent content in the antistatic composition was also insufficient, showed significant changes in surface resistance and water contact angle due to UV irradiation, indicating a lack of UV resistance and changes in the surface characteristics of the antistatic polyester film. In contrast, Comparative Example 4, in which the crosslinking agent content in the antistatic composition was too high, had an excessively large crosslinking density, resulting in a poor appearance and a significant change in the water contact angle after UV treatment, resulting in changes in the surface characteristics of the antistatic polyester film.

[0119] In addition, Comparative Example 5, in which the content of the UV absorber and the free radical scavenger in the antistatic composition was insufficient, showed reduced UV resistance, a significant increase in surface resistance and a significant decrease in water contact angle due to UV treatment. In contrast, Comparative Example 6, in which the content of the UV absorber and the free radical scavenger in the antistatic composition was too high, showed poor film appearance.

[0120] According to the antistatic composition of one embodiment of the present invention as described above and the antistatic polyester film using the same can effectively eliminate the generation of static electricity, especially suppress the generation of foreign matter caused by dust accumulation and the electrical short circuit caused by static electricity, thereby improving productivity. At the same time, the antistatic composition of one embodiment of the present invention and the antistatic polyester film using the same maintain excellent antistatic effect even in subsequent processes (such as UV treatment or another coating process using a solvent) because the surface resistance changes very little. In addition, its water contact angle shows very little change, ensuring the maintenance of surface characteristics and excellent appearance.

[0121] While the invention has been particularly shown and described with reference to exemplary embodiments thereof, it will be understood by those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the invention as defined by the appended claims.

[0122] Reference numerals

[0123] 10: Base

[0124] 20: Antistatic layer

Claims

1. An antistatic composition comprising a conductive polymer resin, a binder resin, a crosslinking agent, an ultraviolet absorber and a free radical scavenger. 2 . The antistatic composition according to claim 1 , wherein the conductive polymer resin comprises an aqueous dispersion containing a polyanion and polythiophene or an aqueous dispersion containing a polyanion and a polythiophene derivative. 3 . The antistatic composition according to claim 1 , wherein the conductive polymer resin has an average particle size of 20 nm to 60 nm. 4 . The antistatic composition according to claim 1 , wherein the binder resin comprises at least one selected from the group consisting of polyurethane, polyester, and acrylic.

5. The antistatic composition according to claim 1, wherein the crosslinking agent comprises a crosslinking agent selected from the group consisting of an isocyanate-based crosslinking agent, a carbodiimide-based crosslinking agent, a At least one of an oxazoline-based crosslinking agent, an epoxy-based crosslinking agent, and a melamine-based crosslinking agent. The antistatic composition according to claim 1 , wherein the ultraviolet absorber comprises a benzotriazole-based compound or a benzophenone-based compound.

7. The antistatic composition according to claim 1, wherein the ultraviolet absorber comprises at least one compound selected from the group consisting of 2-(2H-benzotriazole-2-yl)-4,6-bis(1-methyl-1-phenylmethyl)phenol, bis[2-hydroxy-5-tert-octyl-3-(benzotriazole-2-yl)-phenyl]-methane, 2(2'-hydroxy-3,5'-di-tert-butylphenyl)benzotriazole, 2(2'-hydroxy-3'-tert-butyl-5'-methyl-phenyl)benzotriazole, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, 2,2'4,4'-tetrahydroxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone and 2,2'-methylenebis[6-(2H-benzotriazole-2-yl)-4-(1,1,3,3-tetramethylbutyl)phenol]. 8 . The antistatic composition according to claim 1 , wherein the radical scavenger is a hindered amine-based light stabilizer having an amine functional group and is a polymerization product having a 2,2,6,6-tetramethylpiperidine skeleton. 9 . The antistatic composition according to claim 1 , wherein the antistatic composition comprises 150 to 400 parts by weight of the binder resin and 200 to 800 parts by weight of the crosslinking agent based on 100 parts by weight of the conductive polymer resin. 10 . The antistatic composition according to claim 1 , wherein a weight ratio between the binder resin and the crosslinking agent is 1:1 to 4. 11 . The antistatic composition according to claim 1 , wherein the antistatic composition comprises 15 to 40 parts by weight of the total of the UV absorber and the radical scavenger relative to 100 parts by weight of the binder resin.

12. An antistatic polyester film comprising: Polyester base; as well as An antistatic layer formed by applying the antistatic composition according to any one of claims 1 to 11 to at least one surface of the polyester substrate.

13. The antistatic polyester film according to claim 12, wherein the surface resistance of the antistatic layer is 10 7 Ω / sq or less.

14. The antistatic polyester film according to claim 12, wherein the antistatic layer exhibits a surface resistance change ΔH1 of 1 or less according to the following Formula 1 before and after UV irradiation with a dose of 300 mJ or more: (Formula 1) ΔH1=log[(UV2) / (UV1)] in, UV1 is the surface resistance before UV irradiation, and UV2 is the surface resistance after UV irradiation. 15 . The antistatic polyester film according to claim 12 , wherein the antistatic layer shows a difference in water contact angle of 1.9° or less before and after UV irradiation with a dose of 300 mJ or more.

16. The antistatic polyester film according to claim 12, wherein the antistatic layer shows a surface resistance change ΔH2 of 1.8 or less before immersion in a MEK solvent and after immersion in a MEK solvent for 2 hours according to the following Formula 2: (Formula 2) ΔH2=log[(MEK2) / (MEK1)] in, MEK1 is the surface resistance before MEK immersion, and MEK2 is the surface resistance after MEK immersion.

Citation Information

Patent Citations

  • Antistatic polyester film with acetylenediol surfactant and preparing method thereof

    CN101921540A

  • Weather-resistant light-cured antistatic coating and antistatic product

    CN111253793A

  • Antistatic laminated sheet and its manufacturing method

    JP2006198805A

  • Laminated polyester film

    JP2017218507A

  • Polarizing film having ultraviolet absorption function and fabricating method thereof

    KR1020030053904A